A universal DNA extraction and PCR amplification method for fungal rDNA sequence‐based identification. Issue 10 (27th May 2014) - Romanelli, A. M.; Fu, J.; Herrera, M. L.; Wickes, B. L.
Summary Accurate identification of fungal pathogens using a sequence‐based approach requires an extraction method that yields template DNA pure enough for polymerase chain reaction (PCR) or other types of amplification. Therefore, the objective of this study was to develop and standardise a rapid, inexpensive DNA extraction protocol applicable to the major fungal phyla, which would yield sufficient template DNA pure enough for PCR and sequencing. A total of 519 clinical and culture collection strains, comprised of both yeast and filamentous fungi, were prepared using our extraction method to determine its applicability for PCR, which targeted the ITS and D1/D2 regions in a single PCR amplicon. All templates were successfully amplified and found to yield the correct strain identification when sequenced. This protocol could be completed in approximately 30 min and utilised a combination of physical and chemical extraction methods but did not require organic solvents nor ethanol precipitation. The method reduces the number of tube manipulations and yielded suitable template DNA for PCR amplification from all phyla that were tested.